The olive oil sector in Syria [printed version also available in Arabic] - El Ibrahem A.; Abdine M.; Dragotta A. (Syrian national strategic plan for olive oil quality : final report, 2007)
A summary of the Syrian olive sector is presented, by joint analyses made from statistics available and data taken during the surveys carried out by the Project of 444 farmers and 252 mills in the 8 olive oil producing regions in Syria from 2004 to 2006.